A method of pseudobasis matrices - Kudin, V. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
A method of analysis and optimization of linear systems (in particular, of solution of linear programming problems) is proposed. It is based on the conception of pseudobasis matrices. The necessary theoretical substantiation of the construction of algorithmic schemes is given. The conditions of uniqueness (nonuniqueness) of optimum solutions are found. The method can be applied to problems of large dimensions and to the identification of passive constraints of a model in the course of the iteration process.